Rathke's Cleft Cyst Abscess with a Very Unusual Course - Coulden, Amy; Pepper, Joshua; Juszczak, Agata; Batra, Ruchika; Chavda, Swarupsinh; Senthil, Latha; Ayuk, John; Pohl, Ute; Nagaraju, Santhosh; Karavitaki, Niki; Tsermoulas, Georgios (Asian Journal of Neurosurgery, 2022)
Infected Rathke's cleft cysts (RCC) are extremely rare with only a few published cases. We report the case of a 31-year-old man who presented with headaches, visual disturbance, and hypopituitarism secondary to an infected RCC with extension of abscesses along the optic tract. Magnetic resonance imaging showed ring enhancing cystic lesions within an expanded sella with suprasellar and intraparenchymal extension. The radiological appearance suggested a high-grade optic glioma, but an endoscopic transsphenoidal biopsy revealed frank pus in the pituitary fossa, which subsequently grew Staphylococcus aureus. Pathological examination of the cyst wall showed an inflamed RCC. Following a prolonged course of intravenous antibiotics, the infection resolved and vision improved. RCC abscesses are rare and the intracranial extension of the infection in our case makes it unique.
Keywords: Rathke's cleft cyst; pituitary abscess; transphenoidal surgery